Perceptual-cognitive performance of youth soccer players in a 360°-environment - differences between age groups and performance levels - Ehmann, P.; Beavan, A.; Spielmann, J.; Mayer, J.; Altmann, S.; Ruf, L.; Rohrmann, S.; Irmer, J. P.; Englert, C. (Psychology of Sport and Exercise, 2022)
Introduction An important requirement for soccer players is the accurate and rapid processing of dynamic and complex visual scenes. Therefore, in high-level youth soccer the players` perceptual-cognitive skills are highly relevant from a scientific and practical point of view. The aim of the present study was to investigate differences in perceptual-cognitive performance between youth soccer players of different age groups and soccer performance levels in a dynamic 360°-environment.